2019
DOI: 10.33905/bseusbed.486105
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Ekonomisinde Cari Açık Problemi: Seçili Makroekonomik Değişkenlerle Bir Uygulama

Abstract: The main goal of the countries that want to increase the prosperity of their citizens is economic growth. As a result of worldwide economic and prosperity growth, consumption and energy usage increased significantly. Insufficiency of the local resources lead the countries to international trade. Growth of international trade and increase of financial transactions made the current account deficit (CAD) problem very important for the countries. Therefore, countries develop policies in order to understand the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Çetin (2021) determined the relationship between housing prices, inflation and industrial production index as negative and the relationship between interest rates as positive. Karadas and Salihoglu (2020), while interest rates, housing loan volume, real exchange rate and inflation affect housing prices negatively, the industrial production index creates a positive effect. Zandi et al (2015) found that house prices are mostly affected by interest rates and growth.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Çetin (2021) determined the relationship between housing prices, inflation and industrial production index as negative and the relationship between interest rates as positive. Karadas and Salihoglu (2020), while interest rates, housing loan volume, real exchange rate and inflation affect housing prices negatively, the industrial production index creates a positive effect. Zandi et al (2015) found that house prices are mostly affected by interest rates and growth.…”
Section: Conclusion and Discussionmentioning
confidence: 99%